323Breast and cervical cancer screening and outcomes in NSW mental health service consumers. (2nd September 2021) - Wilson, Elizabeth; Tervonen, Hanna; Currow, David; Sara, Grant
Abstract: Focus of Presentation: This presentation describes methods and findings from the NSW Mental Health Living Longer (MHLL) Program. MHLL involves population-wide data linkage that combines records from nine NSW data collections. Our collection includes over 120 million records for more than nine million people. This presentation focuses on the use of linked data to develop indicators to support reporting on premature cancer mortality for people living with mental illness. We will use these indicators to identify variation in care, assess areas for targeted intervention, and evaluate the effectiveness of research translation into safer and more effective care. Findings: This work will be finalised by August 2020. We will use regression techniques to examine predictors of participation in breast and cervical cancer screening for women who use mental health services in NSW. These results will be used to assess geographical variation in risk-adjusted screening participation rates. We will also present methods and results for measuring incidence and stage at presentation, as well as 12 month and 5 year survival for women who use mental health services compared to other women in NSW. Conclusions/Implications: If cancer survival is a key measure of the effectiveness of healthcare systems, then reduced survival in people with mental health problems reflects less effective health care. Improving screening and treatment services is likely to be the most important strategy for reducing the cancer mortality gap for people with mental illness. Key messages: Health systems must move from recognition to action if we are to reduce premature cancer mortality in people living with mental illness.